Cold acclimation affects immune composition in skeletal muscle of healthy lean subjects - Lans, Anouk A. J. J.; Boon, Mariëtte R.; Haks, Mariëlle C.; Quinten, Edwin; Schaart, Gert; Ottenhoff, Tom H.; Marken Lichtenbelt, Wouter D. (Physiological reports, 2015)
Low environmental temperatures have a profound effect on biological processes in the body, including the immune system. Cold exposure coincides with hormonal changes, which may directly or indirectly alter the immune system, even in the skeletal muscle. The aim of the present study was to investigate the effect of cold acclimation on immune composition in skeletal muscle. Skeletal muscle biopsies were obtained from 17 healthy lean subjects before and after 10 days of mild cold exposure (15°C, 6 h/day). Nonshivering thermogenesis was calculated by indirect calorimetry. We found that cold acclimation increased nonshivering thermogenesis from 10.8 ± 7.5 before to 17.8 ± 11.1% after cold acclimation (P < 0.01), but did not affect plasma catecholamine nor cytokine levels. In contrast, cold acclimation affected mRNA expression of several immune cell markers in skeletal muscle. It downregulated expression of the Th17 markers RORC (−28%, P < 0.01) and NEDD4L (−15%, P < 0.05), as well as the regulatory T‐cell marker FOXP3 (−13%, P < 0.05). Furthermore, cold acclimation downregulated expression of the M2 macrophage markers CCL22 (−50%, P < 0.05), CXCL13 (−17%, P < 0.05) and CD209 (−15%, P < 0.05), while the M1 macrophage marker IL12B was upregulated (+141%, P < 0.05). Cold acclimation also enhanced several markers related to interferon (IFN) signaling, including TAP1 (+12%, P < 0.01), IFITM1/3 (+11%, P < 0.05), CD274 (+36%, P < 0.05) and STAT 2 (+10%, P < 0.05). In conclusion, 10 days of intermittent cold exposure induces marked changes in the expression of immune cell markers in skeletal muscle of healthy lean subjects. The physiological consequences and therapeutic relevance of these changes remain to be determined. 10 days of cold acclimation not only results in enhanced nonshivering thermogenesis, but also induces marked changes in immune cell markers in skeletal muscle of healthy lean subjects. Markers involved in Th17 response and M2 macrophage markers were downregulated, and markers for M1 macrophages were upregulated. Furthermore, immune markers related to IFN signaling were upregulated.